Responses of environmental Amycolatopsis strains to copper stress - Dávila Costa, José Sebastián (2011)
Copper is a redox-active metal which acts as a catalyst in the formation of Reactive Oxygen Species (ROS) encouraging oxidative stress. Protection against oxidants is intrinsic to every living cell, however in stress conditions, cells are forced to increase and expand their antioxidative network. In this work, the novel copper-resistant strain Amycolatopsis tucumanensis and the copper-sensitive Amycolatopsis eurytherma were grown under copper increasing concentrations in order to elucidate the dissimilar effects of the metal on the strains viability, mainly on morphology and antioxidant capacity. Although biosorbed copper encouraged ROS production in a dose-dependent manner in both strains, the increase in ROS production from the basal level to the stress conditions in A. tucumanensis is lesser than in the copper-sensitive strain; likewise, in presence of copper A. eurytherma suffered inexorable morphological alteration while A. tucumanensis was not affected. The levels of antioxidant enzymes and metallothioneins (MT) were all greater in A. tucumanensis than in A. eurytherma; in addition MT levels as well as superoxide dismutase and thioredoxin reductase activities in A. tucumanensis, were higher as higher the concentration of copper in the culture medium. This work has given evidence that an efficient antioxidant defence system might aid microorganisms to survive in copper-stress conditions; besides it constitutes the first report of oxidative stress study in the genus Amycolatopsis and contributes to enlarge the knowledge on the copper-resistance mechanisms of A. tucumanensis.